Characterization Of Sunscreen Containing Zinc Oxide Nanorods For Sunscreen Applications - Zaki, Nur Athirah Ahmad (2018)
The growing applications of zinc oxide (ZnO) material as the main component are found in cosmetic products and sunscreen due to their efficient ability to absorb UV rays in broad spectrum. The main objective in this research work was to characterize sunscreen containing ZnO nanorods at different concentrations using FESEM-EDS, TEM, UV-Visible and FTIR spectroscopy. Rod shape was the dominant structure in the ZnO powder viewed in FESEM and TEM with a width range of 61-70 nm. The average crystallite size of the ZnO nanorods were at 36.7 nm. The base cream of sunscreen was made from mineral oil and beeswax. ZnO powder was added with the concentrations of 5, 10, 15, 20, 25, 30, 35 and 40 wt% into the base cream. The UV-Vis absorbance samples spectra with higher concentration of ZnO nanorods exhibited highest UV absorbance in UV ranges. At 40wt% ZnO nanorods, samples exhibited sharp peak at 376.3 nm with 3.28 eV band energy. The calculated critical wavelength of sunscreen contained ZnO nanorods exhibited a broad-spectrum protection in UVA region. ATR spectra showed no new functional bonds created between base cream and ZnO nanorod particles. The cream/ZnO mixture were stable in that the stability of the sunscreen samples were tested through centrifugation test, color and phase separation for 35 days stored in room temperature. The samples contain 20 to 40 wt% of ZnO nanorods showed stable phase over 35 days storage. The pH determination was determined, and it showed that all concentrations of sunscreen ZnO nanorod exhibited slightly acidic properties (pH 5.95 to 5.61) and had acceptable pH value for human skin application. In summary, the sunscreen contained ZnO nanorods prepared in this work possessed great potential as an effective sunscreen for UVA and UVB protection on human skin.